THE OXFORD ENGLISH DICTIONARY IN MODERN LINGUISTICS AND EDUCATION - Yoqubova Mohichehra,; Xalilova Mohichehra,; Abdullayeva Ruxsora, (TADQIQOTLAR, 2026)
Annotation This article examines the importance of the Oxford English Dictionary (OED) in modern linguistics and education. The OED is widely recognized as one of the most authoritative  and  comprehensive  dictionaries  in  the  world.  It  provides  not  only definitions  of  words  but  also  detailed  historical  records,  including  their  origins, pronunciation, and changes in meaning over time. This study explores how the OED contributes to vocabulary development, critical thinking, and effective communication skills.  In  addition,  it  highlights  the  role  of  the  dictionary  in  connecting  language learning with historical, cultural, and social contexts. The research shows that the OED is not just a linguistic tool but also a valuable educational resource.